2019
DOI: 10.1167/tvst.8.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ability of Macular Vessel Density in the Ganglion Cell–Inner Plexiform Layer on Optical Coherence Tomographic Angiography for Glaucoma

Abstract: Purpose The purpose of this study was to analyze the macular vessel density layer-by-layer and compare the diagnostic value of each in diagnosing glaucoma. Methods This was a prospective comparative cross-sectional study, and the setting was glaucoma referral practice. The study participants were patients with primary open-angle glaucoma undergoing treatment with drugs, and age-matched normal controls who visited our clinic for regular eye examinations for refractive er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It has been stated that abnormal changes in the RGCs soma and dendrites might be observed earlier than the axonal loss in the early stage of glaucoma [18]. This increases the role of GCL combined with RNFL for the assessment of retinal neurodegeneration, which might be the result of retinal blood flow changes causing ischemia and RGC loss seen in Gravesʼ disease [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that abnormal changes in the RGCs soma and dendrites might be observed earlier than the axonal loss in the early stage of glaucoma [18]. This increases the role of GCL combined with RNFL for the assessment of retinal neurodegeneration, which might be the result of retinal blood flow changes causing ischemia and RGC loss seen in Gravesʼ disease [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A study using macular whole image vessel density found that a 0.11 μm/year faster decreasing rate of RNFL was associated with every 1% loss of macular vessel density [ 59 ]. Several studies also found a significant decrease of vessel density and flow density in deep retinal vascular plexus and the whole retina, and the diagnostic ability of glaucoma of the vessel density in the GCIPL might be better than in the superficial vascular plexus [ 49 , 60 , 61 , 62 , 63 , 64 , 65 ]. However, still some studies found that macular vessel density performed no better than OCT GCC thickness in distinguishing early glaucoma from healthy eyes [ 66 , 67 , 68 , 69 ].…”
Section: Emerging Structural Diagnostic Biomarkersmentioning
confidence: 99%